A control policy for scheduled traffic flow system. (October 2017) - Han, Yun-xiang; Huang, Xiao-qiong; Tang, Xin-min; Han, Song-chen
Highlights: This paper proposes a flexible max-plus modeling method for air traffic flow. The control problem can be posed as separation-dependent service rate regulation. Some key features of the presented system optimization model are discussed. Abstract: This paper presented a modeling methodology with the aim of controlling flight flow. By incorporating minimum safety separation time, it was demonstrated that the control of air traffic flow in the terminal control area can be regarded as the planning of different departure queues in each fix. The jet route control model for different scenarios were put forward by formulating various types of constraints emphasized in the air traffic control rules. The inherent relationships for different system variables were acquired and the proposed optimization models were applied to coordinate several different departure air traffic flows in the specified fixes. In addition, some key features of the presented system optimization model were discussed. The proposed max-plus system model has been validated using real traffic flow data and some relevant experimental results were reported. Moreover, the influence of different factors such as temperature, weight, as well as aircraft climbing mode on the system optimization performance were also analyzed which demonstrated the validation of the presented system model.